Scientific Literacy Under the Microscope
VII, 155 p.
Keywords: Scientific literacy is generally valued and acknowledged among educators as a desirable student learning outcome. However, what scientific literacy really means in terms of classroom practice and student learning is debatable due to the inherent complexity of the term and varying expectations of what it means for learning outcomes. To date the teacher voice has been noticeably absent from this debate even though the very nature of teacher expertise lies at the heart of the processes which shape students’ scientific literacy. The chapters that comprise this book tap into the expertise of a group of primary teachers from Our Lady of Good Counsel (OLGC), a primary school that chose to actively engage in teaching for scientific literacy. By analyzing the insights and thinking that emerged as they attempted to unravel some of the pedagogical complexities associated with constructing an understanding of scientific literacy in their own classrooms, these teachers demonstrate the professional knowledge and skill inherent in the expertise of teaching and learning science in a primary classroom. The chapters in this book illustrate the processes and structures that were created at OGLC to provide the conditions that allowed these teachers to explore and build on the range of ideas that informed their approach to teaching for scientific literacy. This book is a compelling example of how a whole school approach to scientific literacy can make a difference for students’ learning of science and offer a concrete example of the development of professional knowledge and practice of teachers.